Deep generative models: third MICCAI workshop, DGM4MICCAI 2023 : held in conjunction with MICCAI 2023, Vancouver, BC, Canada, October 8, 2023 : proceedings - Mukhopadhyay, Anirban; Oksuz, Ilkay; Engelhardt, Sandy; Zhu, Dajiang; Yuan, Yixuan (Lecture Notes in Computer Science, 2024)
Methods -- Applications -- Methodology. Causal inference. Latent interpretation. Generative factor analysis -- Mammography. Vessel imaging -- Surgical Videos.